DAKWAH HARAKAH, RADIKALISME, DAN TANTANGANNYA DI INDONESIA - Muhamad Hizbullah (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2018)
The emergence of various movements or militant groups who are on behalf of the current da'wah is not small, it destroys the image and face of Islam. Da'wah should be interpreted as an effort to ground the messages of goodness, peace, and be a solution to all mankind's problems. Da'wah harakah or da'wah movement narrowly defined the activities of da'wah movement that demands total change by involving physical without compromise. In fact, the word harakah contains two insights that besides means movement but also means renewal effort to bring people to a better life. This paper, attempts to discuss how the later misunderstood harah dutwah, and gave birth to radicalism. This paper also tries to provide the da'wah map solution needed to reduce the misunderstandings developed in the community about da'wa and Islam.